2016
DOI: 10.1002/anie.201601448
|View full text |Cite
|
Sign up to set email alerts
|

Astellifadiene: Structure Determination by NMR Spectroscopy and Crystalline Sponge Method, and Elucidation of its Biosynthesis

Abstract: Genome mining of a terpene synthase gene from Emericella variecolor NBRC 32302 and its functional expression in Aspergillus oryzae led to the production of the new sesterterpene hydrocarbon, astellifadiene (1), having a 6-8-6-5-fused ring system. The structure of 1 was initially investigated by extensive NMR analyses, and was further confirmed by the crystalline sponge method, which established the absolute structure of 1 and demonstrated the usefulness of the method in the structure determination of complex h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
5

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 26 publications
4
108
0
5
Order By: Relevance
“…4). Feeding experiments with 13 C-labeled precursors in fungi have suggested the formation of a quiannulatene scaffold via a 5/12/5 tricyclic carbocation and an intriguing cyclobutane intermediate (15,42). With the isolation of tricyclic (5/12/5) and tetracyclic (5/8/6/5) carbocation-derived (−)-variculatriene A (5) and (−)-aleurodiscalene A (9) as minor products of AtTPS25 and Bo250, which produce mainly the quiannulatene scaffold sesterterpenes 4 and 8, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4). Feeding experiments with 13 C-labeled precursors in fungi have suggested the formation of a quiannulatene scaffold via a 5/12/5 tricyclic carbocation and an intriguing cyclobutane intermediate (15,42). With the isolation of tricyclic (5/12/5) and tetracyclic (5/8/6/5) carbocation-derived (−)-variculatriene A (5) and (−)-aleurodiscalene A (9) as minor products of AtTPS25 and Bo250, which produce mainly the quiannulatene scaffold sesterterpenes 4 and 8, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4. Although the astellatene and retigeranin B scaffolds have recently been proposed to also be derived from 5/12/5 tricyclic carbocations (12), previous feeding experiments with 13 C-labeled precursor (43) and our finding that the 11/6/5 scaffold (2) is the major product of AtTPS18 and is present as a very minor product of AtTPS19, -25, and -30 ( Fig. 2C) suggests that the bicyclic C12 carbocation may be diverged into tricyclic 5/12/5 and 11/6/5 cations en route to the formation of pentacyclic sesterterpenes, such as (−)-retigeranin B (3) and (+)-astellatene (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this has been extended to two more clade B-bifunctional terpene synthases, that is, astellifadiene synthase and stellatatriene synthase, which have recently been identified. 19,20 In this study, we developed an efficient method to synthesize sitespecifically isotope-labeled oligoprenyl diphosphate precursors, such as DMAPP, GPP, FPP and GGPP, starting from four chemically synthesized [ 2 H]-IPPs by enzymatic transformation. By using these precursors, we demonstrated that the MS-based analysis of sitespecifically isotope-labeled terpenes provides sufficient information to elucidate the cyclization mechanism catalyzed by PaPS.…”
Section: Ms-based Analysis Of Site-specifically Labeled Terpenesmentioning
confidence: 99%